The Renewable Energy Consumption-Growth Nexus in Central America - Apergis, Nicholas; Payne, J. (Elsevier, 2011)
This study examines the relationship between renewable energy consumption and economic growth for a panel of six Central American countries over the period 1980–2006. The heterogeneous panel cointegration test reveals a long-run equilibrium relationship between real GDP, renewable energy consumption, real gross fixed capital formation, and the labor force with the respective coefficients positive and statistically significant. The results from the panel error correction model indicate bidirectional causality between renewable energy consumption and economic growth in both the short- and long-run.